Edukasi Bijak Bersosial Media Berdasarkan Kaidah Undang-Undang Pada Masyarakat Desa Watesprojo - Ratna Agustina; Aan Andrian; Muhammad Syaifudin; Agus Nur Wijaya; Bella Putra Madya; Dika Lutfi Al Khod’ri; Aisyah Putri Mulyanto; Chamelia Nur Abdillah; Andry Prasetya Gunawan; Berliana Kartika Sari; Ayunda Nurul Safitri; Indra Liliana; Siti Muamalah Ika Nur Marifa; Anas Sobirin; Avrila Rahmadhani Apriandita; Pramudyah Wiji Masruroh; Andrian Lukman; Yuniar Rahma Sacta; Dian Novita Emiliyanti; Muhammad Luis Armando; Dewi Putri Anjani (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2025)
The aim of this community service activity is to provide counseling and evaluation about the importance of law-based education in the use of social media, as well as providing guidance for users to behave ethically and responsibly. The benefit of this social media wise education is that the public gains insight into the impact of media use. social and legal rules governing the use of this platform. The implementation methods we use are observation, socialization and mentoring. This socialization is provided by providing a direct understanding of the impact of using social media based on the laws governing the use of social media, so that people can be wiser in using social media. After the socialization, it is hoped that the public will gain a good understanding of the law, which can help social media users avoid legal problems and increase positive interactions in cyberspace.